POLA KOMUNIKASI ANTARA GUGUS TUGAS DAN TIM RELAWAN PERCEPATAN PENANGANAN COVID-19 DI DESA BALANGTAROANG KECAMATAN BULUKUMPA KABUPATEN BULUKUMBA - Syaiful Novriansyah; Nahdiana Nahdiana (Journal of Communication Sciences (JCoS), 2022)
In an organization, communication has a very great influence on achieving goals. Communication flow would go well if the parties involved in the organization were able to cooperate. This study aims to determine (1) communication patterns between the task force and the volunteer team for the acceleration of covid-19 handling and (2) factors that affected the communication pattern between the task force and the volunteer team for the acceleration of covid-19 handling in Balangtaroang Village, Bulukumpa District, Bulukumba Regency. The research method used qualitative description. Data collection techniques were carried out through interviews, observations, and documentation. Data analysis techniques used methods of reduction, data presentation, and drawing conclusions. The results showed (1) communication patterns between the COVID-19 task force and a team of volunteers in Balangtaroang Village using primary, secondary, linear, and circular communication patterns. These four patterns were considered the most routine and appropriate to be applied in an effort to deal with covid-19 (2) Factors supporting communication patterns between the task force and the volunteer team for the acceleration of handling covid-19 include the involvement of a number of parties consisting of health workers, security, religious leaders, youth leaders, and the community. The obstacles encountered in their communication process were the activeness of the sub-district task force in communicating with volunteers and the sub-district task force, as well as the difficulty of volunteers in convincing the community of the truth of covid-19.